Beyond cardiovascular disease: remnant cholesterol as a novel risk factor for osteoarthritis - Xie, Rui; Chen, Zeping; Zhang, Guimin; Zhao, Wei (Frontiers in Nutrition, 2025)
BackgroundOne of the main causes of impairment in older people globally is osteoarthritis (OA). The importance of metabolic variables in the pathophysiology of OA has received more attention than only mechanical stress. Triglyceride-rich lipoprotein remnants’ cholesterol component, remnant cholesterol (RC), has been linked to a number of metabolic and inflammatory diseases. Its relationship to the risk of OA is yet unknown, though. With an emphasis on the mediating function of body mass index (BMI), the research prospectively investigated the connection of RC levels with incident OA in middle-aged as well as older persons, drawing on data from the English Longitudinal Study of Ageing (ELSA).MethodsParticipants free of OA at baseline were included. RC levels were estimated via the formula: triglycerides/2.2 (mmol/L). The outcome was newly diagnosed OA during follow-up. Cox proportional hazards models were used to examine the association between RC levels and incident OA. The models were adjusted for a range of potential confounders, including age, sex, race, education level, marital status, income, smoking status, alcohol frequency, physical activity level, and chronic comorbidities. Restricted cubic splines (RCS) were leveraged to evaluate dose–response connection. Subgroup analyses tested the robustness of the findings, and bootstrap-based mediation analysis evaluated the indirect effect of BMI.ResultsAmong 2,205 participants, 1,100 incident OA cases were identified during a median follow-up of 13.6 years. Higher RC levels were independently related with higher OA risk (highest vs. lowest quartile: HR = 1.27, 95% CI: 1.07–1.52; per unit increment: HR = 1.01, 95% CI: 1.01–1.03). RCS analysis showed a linear dose–response connection (P for nonlinearity >0.05). Subgroup analyses yielded consistent results without significant interactions (all P-interaction >0.05). Mediation analysis indicated BMI substantially mediated the RC–OA association, accounting for 84% of the effect.ConclusionIn this large prospective cohort of middle-aged and older adults, RC showed a positive, dose–response association with incident osteoarthritis that attenuated to near-null after adjustment for BMI. Mediation analysis indicated that approximately 84% of the total association operated via BMI, supporting adiposity as the principal pathway and suggesting limited BMI-independent effect of RC. These findings highlight RC as a potentially modifiable metabolic biomarker and underscore the interplay of dyslipidemia and obesity in OA pathogenesis, suggesting that RC management combined with weight control may offer an effective strategy for OA prevention.